PEMBELAJARAN PENDIDIKAN AGAMA ISLAM BERBASIS PROBLEM BASED LEARNING - Salsabila, Unik Hanifah; Hendriyarta, Muhammad; Amalia, Tiara Putri; Bakrin, Misbahuszuhrah Ibnu; Mahardika, Hendra (MIDA : Jurnal Pendidikan Dasar Islam, 2023)
Abstract This article discusses the problem-based learning model in Islamic religious education using educational technology. Problem-based learning is a learning model that directs students to solve a problem, and the teacher has to guide the discussion so that it runs smoothly. This study uses data collection methods with literature studies, with the hope of producing a comprehensive understanding and helping readers better understand this phenomenon (learning using problembased learning using educational technology). Islamic religious learning itself is a conscious effort to understand, teach and learn about the Islamic religion. Educational technology according to the general public is synonymous with technology or learning that uses technology only, but educational technology is a tool for solving a problem in the process of teaching and learning activities. Problem-based learning itself is a model in learning that leads to concrete and real problems so that students can think broadly and openly. The collaboration of these two elements leads to very effective learning, and the use of technology can facilitate the delivery of material and receipt of material. Keywords: Islamic religious educational, Educational technology, Problem-based learning Abstrak Artikel ini membahas tentang model pembelajaran problem based learning pada pendidikan agama islam dengan menggunakan teknologi pendidikan. Problem based learning adalah model pembelajaran yang mengarahkan peserta didik untuk memecahkan suatu masalah, dan guru bertugas untuk memandu diskusi agar berjalan dengan lancar. Penelitian ini menggunakan metode pengumpulan data dengan studi kepustakaan, dengan harapannya menghasilkan pemahaman yang komprehensif dan membantu pembaca lebih memahami fenomena tersebut (belajar menggunakan problem based learning menggunakan teknologi pendidikan). Pembelajaran agama islam sendiri adalah usaha yang sadar untuk memahami, mengajar serta mempelajari tentang agama islam. Teknologi pendidikan menurut khalayak umum adalah identik dengan teknologi atau pembelajaran yang menggunakan teknologi saja, akan tetapi teknologi pendidikan pada dasarnya yaitu suatu alat untuk memecahkan suatu permasalahan dalam proses kegiatan belajar mengajar. Problem based lerning sendiri adalah salah satu model dalam pembelajaran yang mengarah pada permasalahan yang konkrit dan juga nyata, agar peserta didik dapat berfikir secara luas dan terbuka. Kolaborasi dari kedua unsur tersebut menyebabkan pembelajaran yang sangat efektif, dan adanya pemanfaatan teknologi dapat mempermudah jalannya penyampaian materi dan penerimaan materi. Kata kunci: Pendidikan agama islam, Teknologi pendidikan, Problem based learning